2013
DOI: 10.1159/000355888
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Induced Potentiation of Peritoneal Macrophage Migration Is Mitigated by Programmed Cell Death Receptor-1 Gene Deficiency

Abstract: The effect of programmed cell death receptor-1 (PD-1) on phagocyte function has not been extensively described. Here we report that experimental mouse sepsis, cecal ligation and puncture (CLP), induced a marked increase in peritoneal macrophage random migration, motility and cell spread, but these changes were lost in the absence of PD-1. Alternatively, phagocytic activity was inversely affected. In vitro cell culture imaging studies, with the macrophage cell line J774, documented that blocking PD-1 with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…Additionally, random migratory capacity (measured both in rate and direction) and cell spreading (following surface adherence) increased markedly after sepsis among WT mice. Importantly, these phenomena were equivalent to findings among sham control samples in the setting of PD-1 gene deficiency (96). These latter changes in migratory capacity, cell spreading and motility, appear to be partly due to PD-1-mediated changes in cytoskeletal alpha-actinin and F-actin aggregation capabilities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Additionally, random migratory capacity (measured both in rate and direction) and cell spreading (following surface adherence) increased markedly after sepsis among WT mice. Importantly, these phenomena were equivalent to findings among sham control samples in the setting of PD-1 gene deficiency (96). These latter changes in migratory capacity, cell spreading and motility, appear to be partly due to PD-1-mediated changes in cytoskeletal alpha-actinin and F-actin aggregation capabilities.…”
Section: Discussionsupporting
confidence: 70%
“…Importantly, these phenomena were equivalent to findings among sham control samples in the setting of PD-1 gene deficiency. 96 to clearance of the invading pathogen. 97 However, it is also thought that the recruitment of activated PMNs may be harmful when these functions are directed at otherwise normal host tissue (bystander injury).…”
Section: Secreted Inhibitorsmentioning
confidence: 99%
“…Although more studies are being performed to investigate the roles of cell surface co-inhibitory molecules in critically ill patient and animal models, few investigators have considered whether these molecules function alone or cooperatively in vivo with other cell surface molecules and/or if there is functional redundancy between each molecule [88]. Most of what we know about these molecules as suggested therapies, particularly CTLA-4, and PD-1, has come from clinical trials in cancer and studies of their roles in viral infections, suggesting that these two molecules block regulatory T cell effector functions, encourage robust CD8 + T cell responses against tumors and paralyze anti-viral T cell motility [89, 90].…”
Section: Cell Surface Co-inhibitory Molecules Immunomodulation and mentioning
confidence: 99%
“…For example, it has also been proposed that PD-L1 expression in the liver plays a role in attenuating acute liver injury in sepsis animal models [91, 92]. Based on experimental animal and human data with PD-1, we propose that an ideal anti-PD-1 therapy in sepsis would enhance monocyte/macrophage phagocytic function as well as T cell function, because the expression of PD-1 on macrophages/monocytes potentially also leads to sepsis-induced immune dysfunction (Figure 4) [36, 88]. …”
Section: Cell Surface Co-inhibitory Molecules Immunomodulation and mentioning
confidence: 99%
“…Recent studies suggest that coinhibitory receptors, including PD-1, cytotoxic T-lymphocyte-associated protein-4, and Band T-lymphocyte attenuator, appear to be important in contributing to sepsis-induced immunosuppression (33,38). Our laboratory reported that mice deficient in PD-1 have increased bacterial clearance and improved survival in experimental sepsis (4,18,30). In response to infection, the liver clears the blood of bacteria and produces cytokines.…”
mentioning
confidence: 98%